Association of H-Type Hypertension with Stroke Severity and Prognosis. (9th September 2018) - Li, Tan; Zhu, Jiajia; Fang, Qi; Duan, Xiaoyu; Zhang, Mingzhi; Diao, Shanshan; Zhou, Yun; Yang, Si; Kong, Yan; Cai, Xiuying
Abstract : Background. The correlation between H-type hypertension and acute ischemic stroke remains uncertain. Objective. The present study was designed to explore the possible relationship between H-type hypertension and severity and prognosis of acute ischemic stroke. Method. We included 372 patients with acute ischemic stroke and divided them into four groups: H-type hypertension group, simple hypertension group, simple hyperhomocysteinemia (HHcy) group, and the control group. NIHSS score was measured at both admission and two weeks later. mRS score, stroke recurrence, cardiovascular event, or all-cause mortality was recorded at 3-month and 1-year follow-up. Result. The results showed that the NIHSS score on admission in the H-type hypertension group (6.32 ± 5.91) was significantly higher than that in the control group (3.97 ± 3.59) (P < 0.05), while there was no obvious association between H-type hypertension and NIHSS score after 2-week treatment (P = 0.106). Endpoint events incidence in H-type hypertension group was the highest; however, in the cox regression model of multiple factor analysis, H-type hypertension was not an independent risk factor. Conclusion. H-type hypertension may result in early functional deterioration and higher incidence rate of endpoint events but not act as an independent risk factor.